The effect of chronic total coronary occlusion percutaneous coronary intervention on absolute perfusion in remote myocardium. (14th October 2021) - De Winter, R W; Schumacher, S P; Van Diemen, P A; Jukema, R A; Somsen, Y B O; Stuijfzand, W J; Bom, M J; Everaars, H; Van Rossum, A C; Van De Ven, P M; Verouden, N J; Danad, I; et al.
Abstract: Background: Successful revascularization of a chronic total coronary occlusion (CTO) impacts coronary physiology of the remote myocardial territory. Purpose: This study evaluated the effect of CTO percutaneous coronary intervention (PCI) on changes in absolute perfusion in remote myocardium as assessed by serial [15O]H2O positron emission tomography (PET) perfusion imaging. Methods: A total of 164 patients underwent [15O]H2O PET imaging at baseline and 3 months after successful single-vessel revascularization of a CTO to evaluate changes in hyperemic myocardial blood flow (hMBF) and coronary flow reserve (CFR) in the remote myocardial territory supplied by both non-target coronary arteries. Results: Remote hMBF and CFR improved (2.29±0.67 to 2.48±0.75 mL min –1 g –1 and 2.48±0.76 to 2.74±0.85, respectively) after CTO revascularization (p<0.01 for both). Absolute perfusion indices in the CTO vessel and the remote myocardium showed a positive linear correlation, both before (r=0.75, p<0.01 and r=0.77, p<0.01 for hMBF and CFR, respectively) and after (hMBF: r=0.87, p<0.01 and CFR: r=0.81, p<0.01) CTO PCI. Absolute increases in remote myocardial perfusion were largest in patients with a higher increase in hMBF (βeta [β] 0.56; 95% CI: 0.47–0.65; p<0.01) and CFR (β 0.51 (0.42–0.60); p<0.01) in the CTO territory, independent of clinical, angiographic and procedural characteristics. Furthermore, baseline (hMBF: β −0.24 (−0.39, −0.08); p<0.01 and CFR: β −0.26 (−0.41, −0.11); p<0.01) and post-PCI perfusion (hMBF: β 0.36; (0.27, 0.46); p<0.01 and CFR: β 0.30 (0.21, 0.40); p<0.01) in the CTO vessel were independently associated with the increase in remote myocardial perfusion after CTO PCI. Conclusions: An overall increase in remote myocardial perfusion was observed following CTO PCI. Absolute perfusion indices in the remote myocardium showed a positive linear correlation with perfusion in the CTO vessel, before and after CTO revascularization. Importantly, baseline, post-PCI and the absolute increase in perfusion in the CTO territory were independently associated with increases in remote myocardial perfusion after revascularization. Funding Acknowledgement: Type of funding sources: None.